Assessment of the efficiency of a trophic state index in determining the water quality of public water supply reservoirs - Vieira Rego da Silva, Daniel Clemente; Queiroz, Lucas Goncalves; Alamino, Douglas Alvarez; Fernandes, Juliana Goncalves; Silva, Sheila Cardoso da [UNESP]; Brazil de Paiva, Teresa Cristina; Martins Pompeo, Marcelo Luiz (Assoc Brasileira Engenharia Sanitaria Ambiental, 2018)
The aim of this study consists in the evaluation of the trophic state index (IET) efficacy as a tool in the water quality analysis of three reservoirs. The IET was calculated based on water transparency in the reservoir and on the surface concentrations of chlorophyll-a and total phosphorus (total P). To identify the correlation of the soil use with the reservoir aquatic pollution, the IET calculated for each reservoir was compared to the thematic mapping of land cover based on Landsat TM 5 satellite images from 2010. The main components analysis (ACP), focused on data correlation, was made using the software PAST (R), version 2.16. Initially, the behavior of the parameters associated with the IET was evaluated alone (total P, chlorophyll-a and transparency) on the reservoirs. Then, the other chemical and physical parameters associated with the reservoirs water quality (without the IET) were applied to the ACP. Finally, all the parameters underwent the ACP (IET and all the other parameters in conjunction). The IET used in this research seemed to be self-sufficient in the prediction of water quality using only three parameters (total P, chlorophyll-a and transparency). The satellite images analysis, in conjunction with the IET data, was sufficient to point out the water quality reduction by punctual sources of pollution even in environments with larger preserved vegetal coverage.
Keywords: limnology; reservoirs; trophic state index